(untitled) (Journal of Health Sciences, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) infection or known as coronavirus disease 2019 (COVID-19) is a highly infectious disease that has been declared as a world pandemic by WHO. Although the majority of patients only experience mild symptoms, older patients and those with comorbidities are in the risk of falling into critically ill and even death. This is thought to correlate with systemic inflammatory response and oxidative stress imbalance. N-acetylcysteine (NAC) is recognized as a potent mucolytic, yet its lesser-known function as an antioxidant is a precursor of glutathione. Basic aspects and either in vivo or in vitro studies showed various mechanisms of NAC acting as a counterbalance in viral infections and its role in decreasing inflammation and oxidative stress. High-dose NAC is reported to be effective as an antioxidant in pneumonia, influenza, sepsis, and acute respiratory distress syndrome. Early evidence in COVID-19 patients showed that NAC could be beneficial. This review gives the scientific background in considering NAC as an adjuvant treatment for COVID-19.